Biological characteristics of γδT cells and application in tumor immunotherapy - Zhu, Renhong; Yan, Qian; Wang, Yashu; Wang, Keqiang (Frontiers in Genetics, 2023)
Human γδT cells are a special immune cell type that is present in small quantities in the body, does not require processing and presentation for antigen recognition, and has a non-major histocompatibility complex (MHC)-restricted immune response. It plays an important role in the body's anti-tumor, anti-infection, immune regulation, immune surveillance and maintenance of immune tolerance. This article reviews the generation and development of human γδT cells, genetic characteristics, classification, recognition and role of antigens, and research progress in tumor immunotherapy.